Prospective study on the effect of short-term androgen deprivation therapy on PSMA uptake evaluated with 68Ga-PSMA-11 PET/MRI in men with treatment-naïve prostate cancer - Ettala O; Malaspina S; Tuokkola T; Luoto P; Löyttyniemi E; Boström PJ; Kemppainen J (My University, 2022)
PURPOSE:
Based on in vitro studies, it is known that androgen deprivation therapy (ADT) increases prostate-specific membrane antigen (PSMA) expression. Therefore, we hypothesised that ADT improves the performance of PSMA-PET imaging in primary staging of prostate cancer. The purpose of the study was to demonstrate the time course effect of ADT on PSMA uptake in different types of metastatic lesions evaluated with 68Ga-PSMA-11 PET/MRI.
METHODS:
Nine men with treatment-naïve prostate cancer were enrolled to a prospective, registered (NCT03313726) clinical trial. A 68Ga-PSMA-11 PET/MRI was performed once before and 3 times post-ADT (degarelix, Firmagon). Change of maximum standardised uptake values (SUVmax) in prostate, lymph nodes, bone metastases, and physiologically PSMA-avid organs were evaluated in a time frame of 1-8 weeks.
RESULTS:
All patients reached castration levels within 10 days, and 50% decrease in prostate-specific antigen (PSA) concentration was observed 14 days post-ADT. A heterogeneous increase in PSMA uptake was observed 3 to 4 weeks post-ADT. This phenomenon was definitively more evident in bone metastases: 13 (57%) of the metastasis, with a mean (range) SUVmax increase of 77% (8-238%). In one patient, already having bone metastases at baseline, three new bone metastases were observed post-ADT. Of lesions with reduced SUVmax, none disappeared.
CONCLUSIONS:
Both in patient and region level, increase in PSMA uptake post-ADT is heterogenous and is seen most evidently in bone metastases. Preliminary results on a small cohort of patients suggest the clinical impact of ADT on improving the performance of 68Ga-PSMA PET in staging seems to be minor. However, the optimal imaging time point might be 3 to 4 weeks post-ADT. Since none of the metastases with decreasing SUVmax disappeared, it seems that short-term usage of ADT does not interfere with the interpretation of 68Ga-PSMA PET.
TRIAL REGISTRATION:
NCT03313726, registered 18 October 2017; EUDRA-CT, 2017-002345-29.